PERAN NEGOSIASI DALAM PROSES PENGAMBILAN KEPUTUSAN KONSUMEN UNTUK MENYEWA KAMILA KOST EXCLUSIVE - Hasna Kamila; Cecep Safa’atul Barkah; Nurillah Jamil Achmawati (Jurnal Administrasi Bisnis, 2024)
This study aims to explore the role of negotiation in the decision-making process of consumers renting at Kamila Kost Exclusive. Using a descriptive qualitative approach, the research describes and deeply understands the phenomena of negotiation and consumer decisions. Data were collected through in-depth interviews with the owners and tenants, as well as participatory observations. The results indicate that negotiation helps consumers evaluate various options based on criteria such as rental duration, price, and installment terms. Effective negotiation enables consumers to obtain better deals, ensuring their satisfaction and loyalty. The management of Kamila Kost Exclusive needs to enhance their negotiation skills, offer flexibility in rental policies, and maintain transparent communication with tenants for sustainable business success.